Aplikasi Penentuan Penerbit Buku Sekolah Terbaik Dengan Menggunakan Metode Topsis Berbasis Web - Yenny Ratna Sari; Gusvina Fransiska; M. Diarmansyah Batubara (Query: Journal of Information Systems, 2019)
The book is the result of analysis of knowledge made in writing. Books are important for students who are studying in school, so it is important for schools choose the right books so that students can be given the right knowledge. In this era of modern times as many books are spread with all kinds and kinds of topics and of course with different publishers as well, therefore choosing a quality book is a key to bringing students to become qualified students. Because of the large number of book publishers available, schools find it difficult to determine a quality standard book. So in this problem the Topsis method was created to determine the best school book publishers. This Topsis method can help the school to make the right and accurate results, so that it can reduce the problems that exist in the school. Using web based application, it is certainly easier to access, to choose the best school books publishers.Keywords:  Web, Best Book Publishers, Topsis, Decision Support Systems.